The relationship between ants (Hymenoptera: formicidae), vine mealybug (Hemiptera: pseudococcidae) and parasitoids in vineyards of the Western Cape Province, South Africa - Mgocheki, Nyembezi (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Conservation Ecology and Entomology))--Stellenbosch University, 2008.